Corporate entrepreneurial behaviour, organisational architecture and the entrepreneurial process - Coetzee, Riaan (My University, 2017)
The prominence of international entrepreneurship in the global economy is of great importance and interest to researchers, entrepreneurs and governments alike. International business and accelerated internationalisation focus on multinational companies as well as entrepreneurial ventures for growth and innovative collaborations across borders in the global environment. The dominant logic for any corporate organisation today is to ensure that it facilitates and fosters an ecosystem that is conducive to innovation. The concept of generating opportunity through creativity and exploiting it with innovation, has proved to be extremely difficult, yet valuable. Innovation and control systems balance each other to ensure a pro-entrepreneurial organisational climate. Corporate entrepreneurship (CE) has received substantial attention in entrepreneurship research, which expands and develops a cumulative body of knowledge. The CE strategy is conceptualised by identifying key principles and components. This research is formulated to investigate the pro-entrepreneurial organisational architecture, as well as the entrepreneurial process and behaviour that individually and collectively encourage entrepreneurial orientation (EO). The relationships between the identified variables and moderators in a bank in the financial sector of South Africa are measured. Stevenson’s (1983) dimensions of entrepreneurial management, defined as a set of opportunity-based constructs, was measured by the EM measurement scale. Entrepreneurial orientation (EO) was assessed with the Miller/Covin- Slevin scale and linked to the entrepreneurial or innovative process of the company. Analysis of 178 samples (n=2229) indicated positive relationships between the variables, confirming theories in literature on the effects or predictions of the elements in the CE strategy on each other. The effect of success or failure in implementation indicated no moderating effect. Recommendations to address in future research are suggested.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management, specialising in Entrepreneurship and New Venture Creation Johannesburg, 2016
Keywords: Entrepreneurship--South Africa.; Organizational effectiveness; Business enterprises--South Africa.